The detection and enumeration of Propionibacterium SPP isolated from a kefir beverage using PCR and microbiological methods - Cloete, Lynette (Cape Peninsula University of Technology, 2026)
Malnutrition and vitamin deficiencies remain major global food challenges. To overcome these issues, naturally healthy products are often fortified with beneficial ingredients or probiotics to further enhance their nutritional profile. Kefir is one such example, as it has successfully been fortified with Propionibacterium freudenreichii. This probiotic provides multiple gut health benefits while also producing important micronutrients such as vitamin B12 and folate. Kefir itself is a probiotic-rich beverage that naturally contains a diverse matrix of symbiotic lactic acid bacteria, yeasts, and other beneficial microorganisms. However, secondary yeast fermentation during storage may compromise product stability, potentially leading to nutrient loss and other shelf-life defects. Ensuring that fortified dairy products reach the consumer with their nutrients intact is therefore essential. This remains challenging due to the inherently short shelf life of such products and the time-consuming nature of many conventional microbiological tests. Furthermore, detection of propionibacteria in complex food matrices can be cumbersome and unreliable. The present study aimed to optimise a method to detect P. freudenreichii in kefir during refrigerated, frozen, and freeze-dried storage for 28 days. Conventional enumeration was compared with the polymerase chain reaction (PCR) method. For culture-based analysis, serial dilutions were prepared and plated on YEL, PCA, and Pal-Propiobac. DNA was extracted using the Power Food Microbial DNA Isolation Kit. Because DNA from dead cells may remain intact, leading to false positives, samples were pretreated with propidium monoazide (PMA) prior to extraction. This intercalating dye penetrates non-viable cells, binds to their DNA, and prevents its amplification, ensuring that only viable cells with intact membranes are detected. The PCR protocol was optimised specifically for P. freudenreichii, with amplification of the V3 variable region within the 16S rRNA gene carried out using species-specific primers Prop1 (5′- GATACGGGTGACTTGAGG-3′) and Prop2 (5′-GCGTTGCTGATCTGCGATTAC-3′). Viable P. freudenreichii could be detected in kefir across all storage treatments for up to 28 days with PCR with PMA treatment. Selective enumeration was difficult using PCA and YEL agar due to the complex, diverse microbial flora naturally present in kefir and to exposure to low temperatures. In contrast, Pal-propiobac successfully suppressed competing microbial species, enabling more accurate detection of propionibacteria. Overall, this study highlights that optimised PCR, combined with selective pretreatment and culture-based confirmation, offers a reliable and efficient method for monitoring P. freudenreichii in fortified kefir during storage, thereby ensuring both probiotic integrity and product quality.
Thesis (MSc (Food Science and Technology))--Cape Peninsula University of Technology, 2026